What kind of science for dual diagnosis? A pragmatic examination of the enactive approach to psychiatry - Larsen, Jonathan Led; Johansen, Katrine Schepelern; Mehlsen, Mimi Yung (Frontiers in Psychology, 2022)
The recommended treatment for dual diagnosis - the co-occurrence of substance use and another mental disorder - requires seamless integration of the involved disciplines and services. However, no integrative framework exists for communicating about dual diagnosis cases across disciplinary or sectoral boundaries. We examine if Enactive Psychiatry may bridge this theoretical gap. We evaluate the enactive approach through a two-step pragmatic lens: Firstly, by taking a historical perspective to describe more accurately how the theoretical gap within the field of dual diagnosis initially developed. Secondly, by applying the Enactive Psychiatry approach to data from a longitudinal study on the trajectory of cannabis use in psychosis disorders. By applying the theory rather than simply presenting it, we position ourselves better to evaluate whether it may assist the purpose of achieving a more expedient pragmatic 'grip' on the field of dual diagnosis. In our discussion, we suggest that this may very well be the case. Finally, we consider the enactive approach as one of a small handful of new theories of mental disorders that draw on systems thinking and ecological psychology, and discuss whether they have the potential for a wider progressive problemshift within psychiatry. The case in favour of such potential, we argue, is less strong unless the role of complexity, similar to that seen within the dual diagnosis field, may be demonstrated for other fields of clinical practice.